Billy Elliot [videorecording (DVD)] - Daldry, Stephen; Walters, Julie, 1950-; Lewis, Gary, 1958-; Draven, Jamie; Bell, Jamie, 1986-; Cooper, Adam (Universal Studios, 2001)
Eleven-year-old miner's son Billy Elliot is on his way to boxing lessons when he stumbles upon a ballet class. Billy secretly joins the class, knowing that his blue-collar family would never understand.